SAP SA and CAD House : of conduct and commission - Sieff, Grant; Beswick, Claire (London : Wits Business School, 2019)
Between 2014 and 2017 the management team of the South African division of global software company, Systems, Applications and Products in Data Processing (SAP), managed to exploit loopholes in the group's integrity management systems so as to take advantage of the influence that members of the Gupta family.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Business ethics -- South Africa